Enhancing abscisic acid production in Botrytis cinerea through metabolic engineering based on a constitutive promoter library - Ling-Ru Wang; Ji-Zi-Hao Tang; Shu-Ting Zhu; Na Wu; Zhi-Kui Nie; Tian-Qiong Shi (Synthetic and Systems Biotechnology)
Abscisic acid (ABA) is an important plant growth regulator with broad applications in agriculture, forestry, and other fields. Currently, the industrial production of ABA primarily relies on microbial fermentation using Botrytis cinerea, but its genetic toolbox is limited. To address this, we first screened 10 strong constitutive promoters from the genome of B. cinerea through transcriptomic analysis. The expression levels of the promoters covered a range of 3–4 orders of magnitude according to the measured β-glucuronidase activity. Subsequently, four promoters of different strength were used to balance the cofactor supply in B. cinerea. Overexpression of NADH kinase using the medium-strength promoter Pef1a significantly enhanced ABA production, resulting in a 32.26 % increase compared to the control. Finally, by combining promoter engineering with a push-pull strategy, we optimized the biosynthesis of ABA. The recombinant strain Pthi4:hmgr-Pef1a:a4, overexpressing HMGR under the Pthi4 promoter and Bcaba4 under the Pef1a promoter, achieved an ABA titer of 1.18 g/L, a 58.92 % increase. To our best knowledge, this is the first constitutive promoter library suitable for B. cinerea, providing important tools for the industrial production of ABA.